Conjugalidade financeira: manejo e interferência do dinheiro na vida do casal. - Rodrigues, Helga Costa Carvalho (2018)
Money is part of human development and it is present in all relationships. Economic issues influence the behavior of people, thus presenting refutations in marital relationships. Money has its own meaning for each human being and during the constitution of conjugality a particular way of managing the finances on the part of the couple will be established. In turn, couples may face problems related to financial issues. In this sense, this dissertation sought to understand the influence of money management in the exercise of conjugality, having as specific objectives: a) to analyze the meaning that money has for the individual; b) identify the way of managing the money chosen by the conjugal dyad; c) recognize the existence of possible conflicts faced by the couple, related to financial matters; d) distinguish coping strategies used by the couple in an attempt to resolve possible conflicts over financial issues. This is a qualitative research in which eight subjects participated, being four women and four men (not married to each other), heterosexuals, of middle class, without children, aged between 25 and 40 years. They answered a sociodemographic questionnaire, which had as objective to collect relevant information about the studied public, and an interview conducted in a semi-directed way, composed of questions related to the objectives of the research. The responses to the interview were analyzed based on the thematic content analysis. The main results indicate that: the way couples manage finances influences the exercise of conjugality; the meaning of money is directly influenced by the patterns of financial behavior inherited and taught by the family of origin; financial issues are likely to create conflicts; couples facing economic conflicts use negotiation and dialogue strategies to solve the problem. It is hoped to be able to contribute to broaden the understanding and visibility about this subject, as well as to provide subsidies for the work of professionals dealing with couples in conflicts, since research related to the proposed subject is still scarce in the Brazilian reality.